Peningkatan Kemampuan Membaca Pemahaman dengan Pendekatan Pembelajaran Cooperative Learning Tipe Cooperative Intergrated Reading and Composition (CIRC) pada Siswa Semester 1 SMP Negeri 2 Tanon Tahun Pelajaran 2010/2011 - Sri Handayani (Jurnal Pendidikan, 2011)
The objectives of this research are: (1) to identify the students' reading comprehension skill at SMP 2 Tanon, (2) to depict the obstacles in learning reading comprehension of the students of SMP 2 Tanon, and (3) to describe the implementation of CIRC method in improving students' reading comprehension skill at SMP N 2 Tanon. This research is conducted under Class Action Research design with two cycles in the first semester term 2010/2011. The subjects of this research are the IXth C graders. Data collecting techniques are observation, interview and documentation, which are then analyzed under qualitative method. The results of the analysis shows that CIRC method is sufficiently effective to improve students' achievement in reading comprehension. The indicators are: (1) the students achievement develops significantly, (2) the learining activities become more interactive, which can be seen through the warm discussion conducted in classes, where students share ideas within and among groups (3) the teacher controls the whole learning process intesively.